Novel Switching Design Structure for Three Phase 21-Level Multilevel Inverter Fed BLDC Drive Application - Srinivas Rao Janiga; P. Srinivasa Varma; T. Suresh Kumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Multilevel Inverters offers eminent solutions to high voltage high power applications due to the association of several devices in a series configuration. This is moderate because of getting superior quality voltage waveform when using multilevel inverters as compared to form two-level inverters. Most of the problems raised in this study are the restriction of many switching devices, which can afford high voltage are preferred in the inverter. Here, a novel multilevel inverter topology with no transformers, less number of switching devices and gate drive circuits are proposed. The proposed inverter topologies can valid more voltage levels with favorable advantages such as less number of switching devices and gate driving circuits and also reduce to humble size, agreeable voltage profile. In this paper multilevel converter fed BLDC drive with different voltage levels and simulation analysis is presented. The validity of the proposed three-phase 21-level multilevel inverter fed to BLDC motor drive scheme is verified through Matlab/Simulink Platform.